Influence of operating microscope in the sealing of cervical perforations - Schmidt, Bruna Schwingel; Zaccara, Ivana Maria; Reis Só, Marcus Vinícius; Kuga, Milton Carlos [UNESP]; Palma-DIbb, Regina Guenka; Poli Kopper, Patricia Maria (Wolters Kluwer, 2016)
Context: Accidental root canal perforations are among the main complications of endodontic treatment. Aim: This study evaluated the influence of operating microscope (OM) in the marginal adaptation of mineral trioxide aggregate (MTA) (Angelus® ) and glass ionomer (Vitremer) inserted into cervical perforations. Materials and Methods: Perforations were made in the cervical third of the buccal wall of the root canal in mandibular incisors. Next, the teeth were divided into four groups (N = 10): MG - MTA without OM; VG - Vitremer without OM; MOMG - MTA with OM; VOMG - Vitremer with OM. The perforations were sealed according to the group and the teeth were prepared for analysis by confocal laser scanning microscope. Images of perforation region (1,024∗) were made and the gap presented by the materials was measured using the Image J program. LEXT OLS4100 three dimensional (3D) measuring laser microscope measured the volumetric misfit. Data of gap were analyzed by Kruskal-Wallis and Dunn′s tests. Analysis of variance (ANOVA) and Tukey′s tests compared the volumetric misfits. Results: The results showed lower volume and gap in the interface dentin/material in VOMG compared to the other groups (P < 0.05). Conclusion: The use of OM improved the quality of cervical perforations sealed with Vitremer, being indicated in clinical situations of iatrogenic cervical perforations.
Keywords: Confocal laser scanning microscopy (CLSM); Glass ionomer; Mineral trioxide aggregate (MTA); Operating microscope (OM)